(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Complications of diabetes are very diverse, with peripheral neuropathy of the lower extremities accounting for a high rate. “Bo duong hoan ngu thang” combined with accupressure massage contribute effectiveness in treatment, but it needs to be proven by research. Objectives: Evaluating the effect of Bo duong hoan ngu thang combined with accupressure massage to treat peripheral nerve complications of the lower extremities in patients with type 2 diabetes, and at the same time to monitor effects unwanted. Subjects and methods: Clinical intervention compared before, after treatment and control in 60 patients randomly devided into 2 groups. The study group used "Bo duong hoan ngu thang" combined with acupressure massage and Thioctic Acid. The control group used Thioctic Acid. The study period was 21 days. Criteria to evaluate the results of functional and physical symptoms, traditional medicine, according to the VAS, UKST, SF-36 scales and the blood Glucose index. Results: The study group improved the functional, physical symptoms and traditional medicine better than the control group (p<0,05), reduced VAS score, reduced UKST score, increased SF-36 score (p<0,001), improved blood Glucose index (p>0.05). No side effect was reported. Conclusion: “Bo duong hoan ngu thang” combined with acupressure massage cabbage has a good effect on improving the functional, physical symptoms and traditional medicine, reduced VAS score, reduced UKST score, increased SF-36 score in patients with peripheral neuropathy of the lower extremities due to type 2 diabetes; And safe during the study period.